Development of prosthetic knee for alpine skiing - Demšar, Ivan (Strojniški vestnik, 2011)
Above-knee amputation significantly reduces the amputee's mobility and physical condition that can be built up through training or other sports activities. Alpine skiing is one of them. This paper deals with an above-knee prosthesis, which provides better kinematics of the leg structure. Imitating the kinematics of the human body, we looked for the kinematics of a system that comes closest to imitating natural movement and replace the missing limb to the highest possible degree. Based on the analysis of human leg kinematics and entire human mass system dynamics, a prototype for a special multi-axis prosthetic knee was developed. Measurements of leg movement during skiing were performed, which served as a basis for the concept. The concept was verified by kinematics, dynamics and strength analysis, and a complete geometric model was made. The concept was then verified on a working prototype, tested on a ski slope.
Keywords: alpsko smučanje; dinamika; kinematika; nadkolenska amputacija; protetika; proteze